2018
DOI: 10.3892/ol.2018.9295
|View full text |Cite
|
Sign up to set email alerts
|

Positive expression of ZNF689 indicates poor prognosis of hepatocellular carcinoma

Abstract: The objective of the present study was to investigate the association between zinc finger protein (ZNF) 689 expression and the clinicopathological features and prognosis of hepatocellular carcinoma (HCC). A total of 102 paired HCC and paired non-cancerous tissues, and 16 normal liver tissues were collected. ZNF689 expression was examined in HCC tissues, paired-noncancerous tissues, and normal liver tissues using RT-qPCR and immunohistochemistry analysis, and the association between ZNF689 expression and HCC pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Some ZFPs have also been reported as prognostic factors in HCC. For example, the high expression of ZBTB20 and ZNF689 in HCC patients was strongly associated with poor clinical prognosis as well as high recurrence rates [ 154 , 155 ]. In a latest study, Sun et al revealed that zinc finger protein 2 gene (ZIC2) was able to predict the prognosis of HCC, and ZIC2 was positively correlated with immune infiltration cells in HCC patients [ 156 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some ZFPs have also been reported as prognostic factors in HCC. For example, the high expression of ZBTB20 and ZNF689 in HCC patients was strongly associated with poor clinical prognosis as well as high recurrence rates [ 154 , 155 ]. In a latest study, Sun et al revealed that zinc finger protein 2 gene (ZIC2) was able to predict the prognosis of HCC, and ZIC2 was positively correlated with immune infiltration cells in HCC patients [ 156 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZNF689, also known as TIPUH1, promotes the progression of hepatocellular carcinoma by suppressing the apoptotic signaling, and a high ZNF689 level indicates a poor prognosis of hepatocellular carcinoma [ 59 , 60 ]. Recently, ZNF689 was shown as a direct regulator of pancreatic cancer cell invasion and migration [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ZNF689 is a C2H2 type zinc finger protein (zinc finger proteins, ZNFs), and the abnormal expression of this gene is involved in the occurrence and development of a variety of tumors ( 26 ). The expression of ZNF689 is significantly increased in liver cancer tissues, and the positive expression of ZNF689 protein in liver cancer tissues is significantly related to tumor size ≥10 cm, tumor envelope infiltration, and microvascular infiltration, and may be a new predictor of the prognosis of liver cancer patients ( 27 ). In addition, knocking out ZNF689 can inhibit the proliferation and migration of liver cancer cells.…”
Section: Discussionmentioning
confidence: 99%